Wow! (Who's up to the challenge? 11)

Calculus Level 5

n = 1 ζ ( 2 n ) n ( 2 n + 1 ) 2 2 n = A ln ( B π ) C \displaystyle\sum _{ n=1 }^{ \infty }{ \frac { \zeta (2n) }{ n(2n+1){ 2 }^{ 2n } } } =A\ln(B\pi )-C

where A , B , C A,B,C are positive integers, then find A + B + C A+B+C .


This is a part of Who's up to the challenge? .


The answer is 3.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Wesley Low
Aug 2, 2020

We first change the order of summation and rearrange the expression by partial fractions n = 1 ζ ( 2 n ) n ( 2 n + 1 ) 2 2 n = n = 1 ( 1 n 2 2 n + 1 ) k = 1 1 ( 2 k ) 2 n \sum_{n=1}^{\infty}\dfrac{\zeta\left(2n\right)}{n\left(2n+1\right)2^{2n}}=\sum_{n=1}^{\infty}\left(\dfrac{1}{n}-\dfrac{2}{2n+1}\right)\sum_{k=1}^{\infty}\dfrac{1}{\left(2k\right)^{2n}} = k = 1 n = 1 ( ( 1 4 k 2 ) n n 4 k ( 1 2 k ) 2 n + 1 2 n + 1 ) =\sum_{k=1}^{\infty}\sum_{n=1}^{\infty}\left(\dfrac{\left(\dfrac{1}{4k^2}\right)^n}{n}-4k\dfrac{\left(\dfrac{1}{2k}\right)^{2n+1}}{2n+1}\right) Using the MacLaurin series for ln ( 1 x ) -\ln\left(1-x\right) , we get k = 1 ( n = 1 ( 1 4 k 2 ) n n 4 k ( n = 1 ( 1 2 k ) n n n = 1 ( 1 2 k ) 2 n 2 n ( 1 2 k ) 1 1 ) ) \sum_{k=1}^{\infty}\left(\sum_{n=1}^{\infty}\dfrac{\left(\dfrac{1}{4k^2}\right)^n}{n}-4k\left(\sum_{n=1}^{\infty}\dfrac{\left(\dfrac{1}{2k}\right)^{n}}{n}-\sum_{n=1}^{\infty}\dfrac{\left(\dfrac{1}{2k}\right)^{2n}}{2n}-\dfrac{\left(\dfrac{1}{2k}\right)^{1}}{1}\right)\right) = k = 1 ( ln ( 1 1 4 k 2 ) 4 k ( ln ( 1 1 2 k ) + 1 2 ln ( 1 ( 1 2 k ) 2 ) 1 2 k ) ) =\sum_{k=1}^{\infty}\left(-\ln\left(1-\dfrac{1}{4k^2}\right)-4k\left(-\ln\left(1-\dfrac{1}{2k}\right)+\dfrac{1}{2}\ln\left(1-\left(\dfrac{1}{2k}\right)^{2}\right)-\dfrac{1}{2k}\right)\right) = k = 1 ( ( ln ( 2 k + 1 ) + ln ( 2 k 1 ) 2 ln ( 2 k ) ) 4 k ( ln ( 2 k 1 ) + ln ( 2 k ) + 1 2 ( ln ( 2 k + 1 ) + ln ( 2 k 1 ) 2 ln ( 2 k ) ) ) + 2 ) =\sum_{k=1}^{\infty}\left(-\left(\ln\left(2k+1\right)+\ln\left(2k-1\right)-2\ln\left(2k\right)\right)-4k\left(-\ln\left(2k-1\right)+\ln\left(2k\right)+\dfrac{1}{2}\left(\ln\left(2k+1\right)+\ln\left(2k-1\right)-2\ln\left(2k\right)\right)\right)+2\right) = k = 1 ( 2 ln ( 2 k ) ( ( 2 k + 1 ) ln ( 2 k + 1 ) ( 2 k + 1 ) ( ( 2 k 1 ) ln ( 2 k 1 ) ( 2 k 1 ) ) ) ) =\sum_{k=1}^{\infty}\left(2\ln\left(2k\right)-\left(\left(2k+1\right)\ln\left(2k+1\right)-\left(2k+1\right)-\left(\left(2k-1\right)\ln\left(2k-1\right)-\left(2k-1\right)\right)\right)\right) Notice that this is actually the definite integral of ln x \ln x , i.e. a b ln x d x = b ln b b ( a ln a a ) \int_{a}^{b}\ln xdx=b\ln b-b-\left(a\ln a-a\right) . Substituting this in gives us k = 1 ( 2 ln ( 2 k ) 2 k 1 2 k + 1 ln t d t ) \sum_{k=1}^{\infty}\left(2\ln\left(2k\right)-\int_{2k-1}^{2k+1}\ln t dt\right) = lim n ( 2 k = 1 n ln ( 2 k ) 1 2 n + 1 ln t d t ) =\lim_{n\rightarrow\infty}\left(2\sum_{k=1}^{n}\ln\left(2k\right)-\int_{1}^{2n+1}\ln t dt\right) = lim n ( 2 n ln 2 + 2 ln n ! ( 2 n + 1 ) ln ( 2 n + 1 ) + ( 2 n + 1 ) 1 ) =\lim_{n\rightarrow\infty}\left(2n\ln2+2\ln{n!}-\left(2n+1\right)\ln\left(2n+1\right)+\left(2n+1\right)-1\right) = lim n ln ( ( n ! ) 2 ( 2 e ) 2 n ( 2 n + 1 ) 2 n + 1 ) =\lim_{n\rightarrow\infty}\ln\left(\dfrac{\left(n!\right)^2\left(2e\right)^{2n}}{\left(2n+1\right)^{2n+1}}\right) Since we are taking the limit as n n\rightarrow\infty , we can apply Stirling's approximation for n ! n! , where n ! 2 π n ( n e ) n {n!}\sim\sqrt{2\pi n}\left(\dfrac{n}{e}\right)^n . This gives lim n ln ( ( 2 π n ( n e ) n ) 2 ( 2 e ) 2 n ( 2 n + 1 ) 2 n + 1 ) \lim_{n\rightarrow\infty}\ln\left(\dfrac{\left(\sqrt{2\pi n}\left(\dfrac{n}{e}\right)^n\right)^2\left(2e\right)^{2n}}{\left(2n+1\right)^{2n+1}}\right) = lim n ln ( π ( 2 n ) 2 n + 1 ( 2 n + 1 ) 2 n + 1 ) =\lim_{n\rightarrow\infty}\ln\left(\dfrac{\pi \left(2n\right)^{2n+1}}{\left(2n+1\right)^{2n+1}}\right) = lim n ln ( π ( 1 + 1 2 n ) 2 n + 1 ) =\lim_{n\rightarrow\infty}\ln\left(\dfrac{\pi}{\left(1+\dfrac{1}{2n}\right)^{2n+1}}\right) = ln π lim n ln ( ( 1 + 1 2 n ) 2 n + 1 ) =\ln\pi-\lim_{n\rightarrow\infty}\ln\left(\left(1+\dfrac{1}{2n}\right)^{2n+1}\right) = ln π lim n ln ( ( 1 + 1 2 n ) 2 n ) ln ( ( 1 + 1 2 n ) ) =\ln\pi-\lim_{n\rightarrow\infty}\ln\left(\left(1+\dfrac{1}{2n}\right)^{2n}\right)-\ln\left(\left(1+\dfrac{1}{2n}\right)\right) = ln π ln e 0 =\ln\pi-\ln e - 0 = ln π 1 =\boxed{\ln\pi-1}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...